Candidate-centered politics: an overview of candidates’ evaluation / Nur Aida Haji Kipli and Mohamad Hasimi Abdullah - Kipli, Nur Aida; Abdullah, Mohamad Hasimi (2010)
The participation from the voters determines the propensity of the candidate to win the election. Nevertheless, various arguments from the scholars and political researchers frequently question the main mechanism or approach depicted as a moving body to get more voters to vote in the election. This central issue of this paper is on the candidate-centered politics in motivating participation among voters. This paper also finds that both physical appearances and character traits contribute to the election results. “Men judge generally made by the eye than by the hand, because belongs to everybody to see you, but too few to come in touch with you. Every one sees what you appear to be, few really know what you are.” – Machiavelli